К вопросу о функциональной организации лексического минимума на основе метода коммуникативных задач - Walczak, Jakub; Drużyłowska, Dorota (Studia Rossica Posnaniensia, 2019)
This paper is the result of the work on the lexical minimum of Russian language for bachelors of Russian philology within the context of Task-based Language Teaching method. The text provides a definition of the lexical minimum, presents the main principles of the Task-based Language Teaching. The main part of the article is devoted to the presentation of the principles of selection and organization of the language material included in the proposed lexical minimum.